microRNA are Central Players in Anti- and Profibrotic Gene Regulation during Liver Fibrosis - Noetel, Andrea; Kwiecinski, Monika; Elfimova, Natalia; Huang, Jia; Odenthal, Margarete (Frontiers in Physiology, 2012)
MicroRNA (miRNA) are small non-coding RNA molecules that posttranscriptionally effect mRNA stability and translation by targeting the 3′-untranslated region (3′-UTR) of various transcripts. Thus, dysregulation of miRNA affects a wide range of cellular processes such as cell proliferation and differentiation involved in organ remodeling processes. Divergent miRNA patterns were observed during chronic liver diseases of various etiologies. Chronic liver diseases result in uncontrolled scar formation ending up in liver fibrosis or even cirrhosis. Since it has been shown that miR-29 dysregulation is involved in synthesis of extracellular matrix proteins, miR-29 is of special interest. The importance of miR-29 in hepatic collagen homeostasis is underlined by in vivo data showing that experimental severe fibrosis is associated with a prominent miR-29 decrease. The loss of miR-29 is due to the response of hepatic stellate cells to exposure to the profibrogenic mediators TGF-β and PDGF-BB. Several putative binding sites for the Smad proteins and the Ap1 complex are located in the miR-29 promoter, which are suggested to mediate miR-29 decrease in fibrosis. Other miRNA are highly increased after profibrogenic stimulation, such as miR-21. miR-21 is transcriptionally upregulated in response to Smad-3 rather than Smad-2 activation after TGF-β stimulation. In addition, TGF-β promotes miR-21 expression by formation of a microprocessor complex containing Smad proteins. Elevated miR-21 may then act as a profibrogenic miRNA by its repression of the TGF-β inhibitory Smad-7 protein.